HAEMATOLOGICAL INDICES AND SERUM BIOCHEMISTRY OF BROILER CHICKEN FINISHER FED DIETS CONTAINING DRIED AVOCADO PEAR SEED (Persea americana) - Akinduro, Victor Olabisi (Journal of Agricultural Sciences (Belgrade), 2021)
ABSTRACTThe general acceptability of plants with proven records of medicinal values in the tropics in recent time, necessitated the use of dried Avocado pear in broiler diet and its possible effects on haematological variables and biochemical indices, the study focused on haematological and biochemical responses of broilers to varying level of inclusion of dried avocado pear seed. The inclusion levels were 0% of the dried Avocado pear seed as control, 2.5%, 3.5%, 4.5% and 5.5%. The experiment lasted for eight weeks, four weeks for the starter phase (for acclimatization of the birds and maturation of their GIT) and four weeks for the test trials (finisher phase). The result showed that there were significant differences (P